2018
DOI: 10.1021/jacs.7b11044
|View full text |Cite
|
Sign up to set email alerts
|

Origins of the Mechanochemical Coupling of Peptide Bond Formation to Protein Synthesis

Abstract: Mechanical forces acting on the ribosome can alter the speed of protein synthesis, indicating that mechanochemistry can contribute to translation control of gene expression. The naturally occurring sources of these mechanical forces, the mechanism by which they are transmitted 10 nm to the ribosome's catalytic core, and how they influence peptide bond formation rates are largely unknown. Here, we identify a new source of mechanical force acting on the ribosome by using in situ experimental measurements of chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 75 publications
6
83
1
Order By: Relevance
“…can generate a maximal force of 15-20 pN on the AP, Fig. 4, in line with theoretical estimates based on MD simulations 46,47 .…”
Section: Discussionsupporting
confidence: 88%
“…can generate a maximal force of 15-20 pN on the AP, Fig. 4, in line with theoretical estimates based on MD simulations 46,47 .…”
Section: Discussionsupporting
confidence: 88%
“…The linker lengths used in these simulations were chosen such that they bracketed the length at which the midpoint of folding occurred. It was recently found that the unfolded state of a nascent chain can generate an entropic pulling force on the ribosome 7 , and attractive interactions between the nascent chain and outer ribosome surface also have the potential to give rise to forces 22 . To isolate the force arising from domain folding we ran additional simulations in which the domains always remain unfolded (see SI Appendix) and simulated these folding-incompetent proteins on arrested ribosomes at the same linker lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Tensile forces acting on the nascent protein can alter the speed of translation elongation in a form of mechanical allosteric communication that links what happens outside the exit tunnel to the ribosome's catalytic core [1][2][3][4][5][6][7] . It has been found that protein folding on translationally arrested ribosomes can generate a pulling force that is transmitted through the nascent protein backbone to the peptidyl transferase center (PTC), which can alter peptide bond formation 1,4,7 . Specifically, a previous study used Quantum Mechanics/Molecular Mechanics simulations to show that pulling forces applied to the PTC can decrease the free energy of the transition state barrier to peptide bond formation 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations